Market Structure and Innovation - Loury, Glenn C. (Quarterly Journal of Economics, 1979)
I. Introduction, 395.—II. The model, 397.—III. Competitive entry and long-run equilibrium, 402.—IV. Welfare analysis of industry equilibria, 405.—V. Conclusion, 408.